SISTEM ANALISIS KERANJANG BELANJA DALAM MANAJEMEN TATA LETAK PRODUK PADA MINIMARKET DENGAN ALGORITHMA APRIORI - Komang Kurniawan Widiartha (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2019)
Coco Mart which is one of the retail network brands engaged in household needs is acompany from PT. Bali Pawiwahan (Coco Group). As time goes on, transaction datacontinues to multiply and cannot be utilized by managerial parties to process transaction data that continues to grow every time. From transaction data, there is information or knowledge that can be extracted. The results of the research conducted, the construction of a shopping basket analysis system to process sales transaction data over the past four years, starting from 2013 with the aim of knowing consumer spending patterns. So that the Shopping Cart Analysis System can be a decisions support in business strategies to regulate the layout of goods and promote product combinations that are often purchased by Coco Mart Jimbaran customers.